GLOBAL MIGRATION SEBAGAI SOLUSI JEPANG DALAM MENGHADAPI AGING POPULATION MELALUI THE IMMIGRATION CONTROL AND REFUGEE RECOGNITION ACT - Fitri Sholihin (TRANSBORDERS: International Relations Journal, 2022)
Aging population is a serious challenge for the Japanese Government. The increasing proportion of the elderly in the population and slower population growth are the basic reasons behind Japan's aging population. The challenges with the aging population have affected Japan's economic performance by increasing the burden and social security benefits. The Japanese government said that this challenge had become a "national crisis". In 2018, the Japanese Government issued an amendment to the migration control law, namely the Immigration Control and Refugee Recognition Act, which is one of Japan's new steps to open up to foreigners. The existence of this law as a control to bring in foreigners with high and low skills. The policy is expected to be able to fill the jobs left behind. In bringing in foreigners as workers, Japan cooperates with several Asian countries such as Vietnam, China, the Philippines, Indonesia, Thailand, Myanmar, Cambodia, and Taiwan. Through this policy, it is hoped that Japan can promote foreign direct investment (FDI) as part of Abenomics reform.